2018
DOI: 10.3928/23258160-20180129-02
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Stereotactic Radiotherapy for Treatment of Exudative Age-Related Macular Degeneration in a Treat-and-Extend Regimen

Abstract: Low-energy SRT, combined with anti-VEGF TER, was associated with reduced injection frequency and preserved VA during 12 months of follow-up. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:86-93.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…The SRT group showed a reduction of anti-VEGF treatment during the 2 years of observation [ 5 ]. The same clinical outcome was shown in a 12-month real-life analysis [ 6 ]. However, a follow-up of the INTREPID trial reported retinal microvascular abnormalities (MVA) in about 30% of eyes, 3 years after SRT [ 7 ].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The SRT group showed a reduction of anti-VEGF treatment during the 2 years of observation [ 5 ]. The same clinical outcome was shown in a 12-month real-life analysis [ 6 ]. However, a follow-up of the INTREPID trial reported retinal microvascular abnormalities (MVA) in about 30% of eyes, 3 years after SRT [ 7 ].…”
Section: Introductionsupporting
confidence: 68%
“…This noninvasive system comprises a precision-controlled X-ray tube, a patient interface, an eye stabilizing device, an eye-tracking system, a graphical user interface, and software for treatment planning. The IRay® System [ 10 ] and the procedure in our setting have been described in full previously [ 6 ] and were approved for clinical use in Europe. Three sequential beams converged to the retina and delivering a 16-Gy dose to an area of 4 mm in diameter centered to the fovea were applied.…”
Section: Case Report/case Presentationmentioning
confidence: 99%
“…All patients had a history of anti-VEGF pretreatment prior SRT (37.6±21.4 months; 26.1±2.4 anti-VEGF pretreatments; 60%/40% receiving aflibercept/ranibizumab). For detailed baseline characteristics, see Hatz et al 17 The previous to SRT used anti-VEGF TER was continued during follow-up: for 48/50 eyes follow-up was available up to 36 months after SRT, and 2/50 eyes were lost to follow-up between 24 and 36 months. All patients attended a safety visit 24±4 months (range 18-33 months) after SRT.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Therefore, different adjunct treatments aiming to reduce anti-VEGF treatment frequency have been considered, such as verteporfin photodynamic therapy 10 11 or radiation therapy. [12][13][14][15][16][17] Generally, there are two types of radiotherapy being reported in nAMD: the external and the internal type. In the external type, called teletherapy, an individually conformed radiation beam of an external source is projected into the target tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation